A Vacuolar Membrane Ferric-Chelate Reductase, OsFRO1, Alleviates Fe Toxicity in Rice (Oryza sativa L.) - Li, Lin; Ye, Lingxiao; Kong, Qihui; Shou, Huixia (Frontiers in Plant Science, 2019)
Ferric reductase oxidase (FRO), the enzyme that reduced ferric iron [Fe (III)] into ferrous iron [Fe (II)], is known to play important roles in Fe absorption and homeostasis in plants that utilize a strategy I mechanism to obtain iron. Rice can use both strategies I and II for Fe uptake depending on the growth conditions. FRO is encoded by two genes in rice genome. Amino acid sequence alignment shows that OsFRO1 contains all necessary predicted motifs for a functional FRO enzyme, whereas OsFRO2 lacks a complete transmembrane domain at the N-terminal. Transient expression of OsFRO1: GFP protein fusion revealed that OsFRO1 is localized to the vacuolar membrane in rice protoplast. OsFRO1 is primarily expressed in leaves and transcript abundance was decreased under excess Fe conditions. Transgenic plants overexpressing OsFRO1 were more sensitive to Fe toxicity, in contrast RNA interference lines showed more tolerance to Fe excess stress. Furthermore, RNAi lines showed decreased Fe concentrations compared to wild type plants under Fe excess condition. Together these data show that OsFRO1 is involved in reducing ferric Fe into ferrous Fe in the vacuole, and makes the vacuolar stored Fe available to the cytoplasm through Fe (II) or chelated Fe (II) transporters. Under Fe excess condition, the downregulation of OsFRO1 in the RNAi plants reduced the amount of Fe (II) available for cytoplasm, to alleviate Fe excess toxicity. This indicates that OsFRO1 plays an important role to maintain Fe homeostasis between the cytoplasm and vacuole in rice.